Impact of drafting on race outcome in the Paris Olympics 1500-m Final: A retrospective analysis of Ingebrigtsen and Hocker using the D' Balance Model - Bellenger, C. R.; Mitchell, L.; Bartram, J. C. (International Journal of Sports Physiology and Performance, 2026)
Purpose: The men`s athletics 1500-m final of the Paris Olympics was won by Cole Hocker in 3:27.65 minutes:seconds.milliseconds. Interestingly, defending Olympic Champion and prerace favorite Jakob Ingebrigtsen led for ~1450 m before being overran by Hocker, who drafted his way through the race, taking the lead with ~50 m to run. Given the contrasting strategies employed, this study explored the impact of drafting on D' balance and predicted finish times for determining the race outcome between Ingebrigtsen and Hocker.